Genome‐wide CRISPR knockout screens identify NCAPG as an essential oncogene for hepatocellular carcinoma tumor growth. Issue 8 (25th April 2019) - Wang, Yu; Gao, Bin; Tan, Peng Yang; Handoko, Yohana Ayupriyanti; Sekar, Karthik; Deivasigamani, Amudha; Seshachalam, Veerabrahma Pratap; Ouyang, Han‐Yue; Shi, Ming; Xie, Chan; Goh, Brian Kim Poh; Ooi, London Lucien; et al.
ABSTRACT: Hepatocellular carcinoma (HCC) is a common and deadly cancer with limited treatment options. Through genome‐wide growth depletion screens using clustered regularly interspaced short palindromic repeats and expression profiling of primary HCC tumors, we identified 13 clinically relevant target genes with therapeutic potential. Subsequent functional annotation analysis revealed significant enrichment of these 13 genes in the cell cycle, cell death, and survival pathways. Non–structural maintenance of chromosomes condensin I complex subunit G (NCAPG) was ranked the highest among the depletion screens and multiple HCC expression datasets. Transient inhibition of NCAPG using specific small interfering RNAs resulted in a significant reduction in cell growth, migration, and the down‐regulation of mitochondrial gene expression in vitro . Small homologous RNA–mediated knockdown of NCAPG significantly impaired cell viability, caused aberrant mitotic division, fragmented the mitochondrial network, and increased cell death in vitro . HCC cells with a reduced expression of NCAPG formed significantly smaller xenograft tumors in vivo . Importantly, high NCAPG expression was significantly associated with poorer overall and disease‐free survival in HCC patients. High NCAPG expression is a novel prognostic biomarker to predict HCC early recurrence after surgical resection. In conclusion, NCAPG is an essential gene for HCC tumor cell survival. It represents a promising novel target for treating HCC and a prognostic biomarker for clinical management of HCC.—Wang, Y., Gao, B., Tan, P. Y., Handoko, Y. A., Sekar, K., Deivasigamani, A., Seshachalam, V. P., OuYang, H.‐Y., Shi, M., Xie, C., Goh, B. K. P., Ooi, L. L., Hui, K. M. Genome‐wide CRISPR knockout screens identify NCAPG as an essential oncogene for hepatocellular carcinoma tumor growth. FASEB J. 33, 8759–8770 (2019). www.fasebj.org